2009
DOI: 10.1088/1126-6708/2009/03/079
|View full text |Cite
|
Sign up to set email alerts
|

Factorization constraints for soft anomalous dimensions in QCD scattering amplitudes

Abstract: We study the factorization of soft and collinear singularities in dimensionallyregularized fixed-angle scattering amplitudes in massless gauge theories. Our factorization is based on replacing the hard massless partons by light-like Wilson lines, and defining gauge-invariant jet and soft functions in dimensional regularization. In this scheme the factorized amplitude admits a powerful symmetry: it is invariant under rescaling of individual Wilson-line velocities. This symmetry is broken by cusp singularities i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
503
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 359 publications
(518 citation statements)
references
References 77 publications
15
503
0
Order By: Relevance
“…At two-loop order we have [8][9][10][11]22] 10) where the H (2) l depend on the flavour of the parton, 11) JHEP02(2015)077…”
Section: Jhep02(2015)077mentioning
confidence: 99%
See 1 more Smart Citation
“…At two-loop order we have [8][9][10][11]22] 10) where the H (2) l depend on the flavour of the parton, 11) JHEP02(2015)077…”
Section: Jhep02(2015)077mentioning
confidence: 99%
“…They are sufficient to understand the infrared singular structure of real radiation contributions at next-to-leading order (NLO) in QCD, and have been instrumental in devising systematic subtraction schemes for NLO calculations [4][5][6]. They also form the starting point for a systematic expansion around unresolved limits to all orders in perturbation theory [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We will show that infrared divergences naturally 'Reggeize', for general t-channel color exchanges, and we will prove that the simplest form of Reggeization breaks down at NNLL accuracy. Interestingly, the general results of Regge theory also have implications on the structure of infrared poles, providing non-trivial constraints on possible corrections to the simplest ansatz for the soft anomalous dimension, the dipole formula [15,16].…”
Section: Pos(ll2012)008mentioning
confidence: 99%
“…Studies performed over the space of several decades (see [17] for a review), and summarized in this context in Refs. [15,18], have shown that infrared singularities factorize. Denoting by M the vector with components M J , one can write [15,16] the matrix equation…”
Section: The Infrared Structure Of Gauge Amplitudesmentioning
confidence: 99%
See 1 more Smart Citation